Organized Crime: Culture, Markets and Policies
VIII, 230 p.
Keywords: Complex interactions of economic, technological, political, and cultural factors have fed the rise of criminal networks worldwide. At the same time, global illegal activities depend on a world of social realities to function. Organized Crime moves beyond traditional concepts of "evil forces" corrupting their host societies, instead analyzing local, national, and international manifestations of organized crime in the situational contexts that aid in its development. The contributors provide up-to-date understanding of various aspects of organized crime, in both classic areas of research (drugs, sex trafficking, labor racketeering) and emerging areas of interest (diamond smuggling, money laundering, eco-crime), in locales as varied as Italy, Quebec, the Sinai, Bulgaria, and the world’s tropical rain forests. Topics are explored from a variety of perspectives, including sociology, criminology, political science, and anthropology, giving this book empirical breadth and depth rarely seen in the literature. A sampling of the topics: Symbolic and economic meanings of crime to cultures. The symbiotic relationships between legitimate and criminal activities. Ethical dilemmas of legitimate businesses with criminal clients. Marketing, problem-solving, recruitment: organizational models of criminal enterprises. Innovative law enforcement/administrative strategies for containing and preventing crime in the U.S. and across Europe. Scholars and researchers of organized crime as well as advanced students of criminology will welcome Organized Crime for coverage that is wide-ranging, comparative, and specific enough to match their interests.